The burden of injury in China, 1990-2017: findings from the Global Burden of Disease Study 2017 - Duan Leilei, MD; Ye Pengpeng, MPH; Juanita A Haagsma, PhD; Jin Ye, MSc; Wang Yuan, PhD; Er Yuliang, MPH; Deng Xiao, MD; Gao Xin, MD; Ji Cuirong, MPH; Wang Linhong, PhD; Marlena S Bannick, BS; W Cliff Mountjoy-Venning, BS; et al. (Elsevier, 2019)
Summary: Background: A comprehensive evaluation of the burden of injury is an important foundation for selecting and formulating strategies of injury prevention. We present results from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017 of non-fatal and fatal outcomes of injury at the national and subnational level, and the changes in burden for key causes of injury over time in China. Methods: Using the methods and results from GBD 2017, we describe the burden of total injury and the key causes of injury based on the rates of incidence, cause-specific mortality, and disability-adjusted life years (DALYs) in China estimated using DisMod-MR 2.1. We additionally evaluated these results at the provincial level for the 34 subnational locations of China in 2017, measured the change of injury burden from 1990 to 2017, and compared age-standardised DALYs due to injuries at the provincial level against the expected rates based on the Socio-demographic Index (SDI), a composite measure of development of income per capita, years of education, and total fertility rate. Findings: In 2017, in China, there were 77·1 million (95% uncertainty interval [UI] 72·5-81·6) new cases of injury severe enough to warrant health care and 733 517 deaths (681 254-767 006) due to injuries. Injuries accounted for 7·0% (95% UI 6·6-7·2) of total deaths and 10·0% (9·5-10·5) of all-cause DALYs in China. In 2017, there was a three-times variation in age-standardised injury DALY rates between provinces of China, with the lowest value in Macao and the highest in Yunnan. Between 1990 and 2017, the age-standardised incidence rate of all injuries increased by 50·6% (95% UI 46·6-54·6) in China, whereas the age-standardised mortality and DALY rates decreased by 44·3% (41·1-48·9) and 48·1% (44·6-51·8), respectively. Between 1990 and 2017, all provinces of China experienced a substantial decline in DALY rates from all injuries ranging from 16·3% (3·1-28·6) in Shanghai and 60·4% (53·7-66·1) in Jiangxi. Age-standardised DALY rates for drowning; injuries from fire, heat and hot substances; adverse effects of medical treatments; animal contact; environmental heat and cold exposure; self-harm; and executions and police conflict each declined by more than 60% between 1990 and 2017. Interpretation: Between 1990 and 2017, China experienced a decrease in the age-standardised DALY and mortality rates due to injury, despite an increase in the age-standardised incidence rate. These trends occurred in all provinces. The divergent trends in terms of incidence and mortality indicate that with rapid sociodemographic improvements, the case fatality of injuries has declined, which could be attributed to an improving health-care system but also to a decreasing severity of injuries over this time period. Funding: Bill & Melinda Gates Foundation.